EXTENDED CREDIT OPPORTUNITIES FOR BUSINESS ENTITIES IN CONDITIONS OF IMPORT SUBSTITUTION - N. P. Simaeva (Финансы: теория и практика, 2017)
The article assesses the opportunities for developing credit relations between economic entities in conditions of import substitution industrial policy. The author concludes that there is a need to attract new lenders because of the increased demand for credit products from businesses. Some government agencies may act as lenders, for example, the Industrial Development Fund which activities and lending program are considered in detail in the article. In author’s opinion, the set of measures that necessary and sufficient to extend credit opportunities for business entities in the conditions of import substitution industrial policy, includes the following items: increased availability of credit products for business entities; open information and economic safety for the credit space participants; strategic and indicative planning of the credit policy; increased involvement of Russian banks in financing of the national economy; introducing by the Central Bank of Russia of measures to stimulate bank lending to business entities under co-financing conditions; expanded list of banking institutions engaged in the programs for business financial and credit support; transparency and control of lenders by the government authorities and Bank of Russia.